A toughening functional masterbatch and preparation method thereof
By melting and extruding modified four-point zinc oxide whiskers and polylactic acid in a twin-screw extruder, a toughening functional masterbatch was prepared, which solved the problem of poor toughening effect of existing PLA products, and achieved the improvement of high toughness and flame retardant performance of polylactic acid.
Patent Information
- Application Number
- CN202410113289.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-01-26
AI Technical Summary
The toughening masterbatch for existing PLA products has a single function and the toughening effect needs to be improved.
After the polylactic acid and modified quad-needle zinc oxide whiskers are treated in a vacuum oven and a high-speed mixer, the toughening functional masterbatch is prepared. Modified tetra-acupuncture zinc oxide whiskers are surface modified by hyperbranched polysiloxane, reducing their hydrophilicity, and grafting hyperbranched polysilane on the surface to improve compatibility and interface strength with polylactic acid.
It significantly improves the toughness and flame retardant properties of polylactic acid, and enhances the mechanical properties and safety of PLA products.
Smart Images

Figure BDA0004684163650000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plastic masterbatches, and in particular relates to a toughening functional masterbatch and a preparation method thereof. Background Art
[0002] Polylactic acid (PLA) is a biodegradable material that can replace traditional petroleum-based general-purpose plastics. Although it has high tensile strength and flexural strength, its elongation at break is usually less than 10% and its toughness is poor. This shortcoming greatly limits its scope of application. In order to solve the shortcomings of PLA's high brittleness and low toughness, relevant practitioners have conducted a lot of research on it. Overall, the commonly used PLA toughening modifications are mainly copolymerization modification, plasticization modification and blending modification.
[0003] Copolymerization modification is a modification method based on micromolecular structure. It refers to the process of introducing flexible chain segments into the side chain or main chain of PLA to reduce the regularity of the PLA chain, reduce its crystallization performance or weaken the interaction between its molecular chain bonds, thereby improving the toughness of PLA. However, most of these modification methods have shortcomings such as complex preparation process and high cost.
[0004] Plasticization modification refers to a method of mixing a high-boiling point, low-volatility and non-toxic plasticizer into the PLA matrix to improve the flexibility of PLA, which effectively achieves the toughening of PLA. However, during use, there will be problems with the migration of plasticizers due to poor compatibility with the matrix, and the plasticized PLA usually sacrifices its excellent tensile strength to achieve improved toughness.
[0005] Blending modification refers to mixing PLA with other fillers by melt or solution blending to achieve a combination of excellent properties of each component, thereby improving the toughness of the PLA group. Currently, the most widely used method is to use toughening masterbatch to toughen PLA products and improve their mechanical properties. However, the toughening masterbatch used in existing PLA products has a single function and the toughening effect needs to be improved. Summary of the invention
[0006] The purpose of the present invention is to provide a toughening functional masterbatch and a preparation method thereof, and to solve the problem that the toughening masterbatch used in existing PLA products has a single function and the toughening effect needs to be improved.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A method for preparing a toughening functional masterbatch comprises the following steps:
[0009] The polylactic acid and the modified four-needle zinc oxide whisker were placed in a vacuum oven at 80°C for drying for 0.5-1h, then placed in a high-speed mixer, stirred and mixed at a speed of 900-1000rpm for 8-12min, and then transferred to a twin-screw extruder for extrusion granulation to obtain a toughening functional masterbatch.
[0010] The mass ratio of polylactic acid to modified tetrapod-shaped zinc oxide whisker is 85-90:10-15.
[0011] Furthermore, the temperature of each zone of the twin-screw extruder is: 100-130°C in zone 1, 170-195°C in zone 2, 185-220°C in zone 3, 185-220°C in zone 4, 195-220°C in zone 5, 195-220°C in zone 6, 195-220°C in zone 7, 195-220°C in zone 8, 195-220°C in zone 9, 200-225°C at the die head, and the feeding speed is 25-28rpm.
[0012] The modified tetrapod-shaped zinc oxide whisker is a hyperbranched polysilane grafted tetrapod-shaped zinc oxide whisker, and the hyperbranched polysilane is obtained by hydrolyzing and condensing gamma-glycidyloxypropyltrimethoxysilane, sulfonate-based siloxane and nitrogen-phosphorus-based siloxane.
[0013] Furthermore, the preparation steps of the modified four-needle zinc oxide whiskers are as follows:
[0014] Add tetrapod-shaped zinc oxide whiskers, acetic acid aqueous solution and anhydrous ethanol into a flask, disperse by ultrasonic for 1 hour, control the temperature at 70-75°C, add hyperbranched monomer, keep the temperature for 24 hours, filter, wash the filter cake with distilled water and dry it under vacuum at 60°C;
[0015] The mass ratio of tetrapod-shaped zinc oxide whiskers, acetic acid aqueous solution, anhydrous ethanol and hyperbranched monomer is 0.2:1:5-10:2, the hyperbranched monomer is composed of γ-glycidyloxypropyltrimethoxysilane, sulfonate-based siloxane and nitrogen-phosphorus-based siloxane in a mass ratio of 1:0.2-0.4:0.6-0.8, and the mass fraction of acetic acid aqueous solution is 60-70%.
[0016] Tetrapod-shaped zinc oxide whisker is an inorganic crystal material with a spatial three-dimensional structure and a new composite material reinforcing and toughening agent with excellent mechanical properties. However, it has high hydrophilicity and poor compatibility with a polylactic acid matrix. In this regard, the present invention utilizes an acid-catalyzed hydrolysis method to graft hyperbranched polysiloxane onto the surface of the tetrapod-shaped zinc oxide whisker to reduce its hydrophilicity and obtain modified tetrapod-shaped zinc oxide whisker. The specific mechanism is that the methoxy and ethoxy groups in the hyperbranched monomer undergo a hydrolysis reaction to produce silanol, which then hydrogen bonds with the hydroxyl groups on the surface of the tetrapod-shaped zinc oxide whisker and finally undergoes dehydration condensation. The remaining hydroxyl groups on the silanol undergo dehydration condensation with the silanol produced by the hydrolysis of the hyperbranched monomer, and the dehydration condensation reaction is repeated to finally form a hyperbranched structure.
[0017] Further, the preparation steps of sulfonate siloxane are as follows:
[0018] Add sodium 3-mercapto-1-propane sulfonate to a flask filled with methanol and deionized water, stir evenly to obtain a mixed solution a, control the system to 70°C, and drop a mixed solution b consisting of allylsiloxane, methanol and azobisisobutyronitrile into the flask. After the addition is completed, keep the temperature for reaction for 4-6 hours. After the reaction is completed, cool to room temperature, filter, wash the filter cake with cold methanol several times, and dry it in a vacuum at 50°C for 48 hours.
[0019] Under the action of the initiator azobisisobutyronitrile, the double bond in the allyl siloxane undergoes a thiol-double bond click addition reaction with the thiol group of sodium 3-mercapto-1-propane sulfonate to obtain sulfonate siloxane.
[0020] Furthermore, the molar ratio of sodium 3-mercapto-1-propane sulfonate to allylsiloxane is 1:1, and the amount of azobisisobutyronitrile is 5% of the total mass of sodium 3-mercapto-1-propane sulfonate and allylsiloxane.
[0021] Furthermore, the mass ratio of sodium 3-mercapto-1-propane sulfonate, methanol and deionized water in the mixed solution a is 5-6:100:10.
[0022] Furthermore, the amount of methanol in the mixed solution a is 10 times the mass of allylsiloxane.
[0023] Furthermore, the allylsiloxane is allyltrimethoxysilane and / or allyltriethoxysilane.
[0024] Further, the preparation steps of nitrogen-phosphorus-based siloxane are as follows:
[0025] Under nitrogen protection, DOPO, 1,2-dichloroethane, triethylamine and 3-aminopropyltriethoxysilane were added to a flask. After stirring for 5-10 minutes, carbon tetrachloride was added dropwise to the flask at 0°C. After the addition was completed, the reaction was stirred at 25°C for 23 hours. After the reaction was completed, the product was filtered and rotary evaporated, and then washed with ethanol and 1,2-dichloroethane respectively, and finally distilled and dried at 50°C for 8 hours. During the reaction, the dosage ratio of DOPO, 1,2-dichloroethane, triethylamine, 3-aminopropyltriethoxysilane and carbon tetrachloride was 4.3g:40mL:3.1mL:4.6mL:2.1mL.
[0026] A toughening functional masterbatch is prepared by the above preparation method.
[0027] Beneficial effects of the present invention:
[0028] The invention provides a toughening functional masterbatch, which is obtained by melt extrusion of polylactic acid and modified four-needle zinc oxide whisker. The four-needle zinc oxide whisker is used as a reinforcing and toughening material, and a hyperbranched polysiloxane is used to modify the surface of the four-needle zinc oxide whisker. While reducing the hydrophilicity of the four-needle zinc oxide whisker, a hyperbranched polysilane containing an epoxy group is grafted on the surface of the four-needle zinc oxide whisker. Based on the low viscosity and good organic compatibility of hyperbranched polymerization and the characteristics that the epoxy group can undergo a ring-opening reaction with the terminal carboxyl group or the segment hydroxyl group of polylactic acid, the interface strength between the polylactic acid molecular chain and the four-needle zinc oxide whisker is significantly improved, so that the four-needle zinc oxide whisker can be uniformly dispersed in the polylactic acid resin, and the reinforcing and toughening effect is fully exerted. The hyperbranched polymer on the surface of the modified four-needle zinc oxide whisker contains a flexible silicon oxygen chain and a molecular cavity, which can further improve the toughness of the polylactic acid.
[0029] In addition, the hyperbranched polysilane on the surface of the modified tetrapod-shaped zinc oxide whisker is obtained by hydrolysis and condensation of γ-glycidyloxypropyltrimethoxysilane, sulfonate-based siloxane and nitrogen-phosphorus-based siloxane, and contains flame-retardant elements such as nitrogen, phosphorus, silicon and sulfur. During the combustion process of the composite material, it can absorb heat and decompose by heat to form a non-volatile protective layer on the polymer surface and isolate the air, while releasing non-flammable gases such as carbon dioxide, sulfur dioxide and ammonia, diluting oxygen and combustible cracking gas, effectively solving the problem of polylactic acid being flammable.
[0030] In summary, the modified tetrapod-shaped zinc oxide whiskers effectively improve the toughness and flame retardant properties of polylactic acid. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The polylactic acid in the following raw materials was purchased from the PLA raw material produced by NatureWorks, USA, with the brand number 4032D.
[0033] Example 1
[0034] This embodiment provides a modified four-needle zinc oxide whisker, and the preparation steps are as follows:
[0035] 0.2 kg of tetrapod-shaped zinc oxide whiskers, 1 kg of acetic acid aqueous solution and 5 kg of anhydrous ethanol were added into a flask, and after ultrasonic dispersion for 1 hour, the temperature was controlled at 70°C, 2 kg of hyperbranched monomer was added, and the reaction was kept warm for 24 hours. The filter cake was washed with distilled water and then vacuum dried at 60°C. The mass fraction of the acetic acid aqueous solution was 66.7%, and the hyperbranched monomer was composed of γ-glycidyloxypropyltrimethoxysilane, sulfonate-based siloxane and nitrogen-phosphorus-based siloxane in a mass ratio of 1:0.2:0.8.
[0036] The preparation steps of sulfonate siloxane are as follows:
[0037] Add 5 kg of sodium 3-mercapto-1-propane sulfonate into a flask containing 100 kg of methanol and 10 kg of deionized water, stir evenly to obtain a mixed solution a, control the system to 70°C, and drop a mixed solution b consisting of 4.5 kg of allyltrimethoxysilane, 45 kg of methanol and 0.475 kg of azobisisobutyronitrile into the flask. After the addition is completed, keep the temperature for reaction for 4 hours. After the reaction is completed, cool to room temperature, filter, wash the filter cake with cold methanol several times, and dry it in vacuum at 50°C for 48 hours.
[0038] The preparation steps of nitrogen-phosphorus-based siloxane are as follows:
[0039] Under nitrogen protection, 4.3 kg DOPO, 40 L 1,2-dichloroethane, 3.1 L triethylamine and 4.6 L 3-aminopropyltriethoxysilane were added to the flask. After stirring for 5-10 min, 2.1 L carbon tetrachloride was added dropwise to the flask at 0 °C. After the addition was complete, the reaction was stirred at 25 °C for 23 h. After the reaction was completed, the product was filtered and rotary evaporated, and then washed with ethanol and 1,2-dichloroethane respectively, and finally distilled and dried at 50 °C for 8 h.
[0040] Example 2
[0041] This embodiment provides a modified four-needle zinc oxide whisker, and the preparation steps are as follows:
[0042] 0.2 kg of tetrapod-shaped zinc oxide whiskers, 1 kg of acetic acid aqueous solution and 10 kg of anhydrous ethanol were added into a flask, and after ultrasonic dispersion for 1 hour, the temperature was controlled at 75°C, 2 kg of hyperbranched monomer was added, and the reaction was kept warm for 24 hours. The filter cake was washed with distilled water and then vacuum dried at 60°C. The mass fraction of the acetic acid aqueous solution was 66.7%, and the hyperbranched monomer was composed of γ-glycidyloxypropyltrimethoxysilane, sulfonate-based siloxane and nitrogen-phosphorus-based siloxane in a mass ratio of 1:0.4:0.6.
[0043] The preparation steps of sulfonate siloxane are as follows:
[0044] Add 6 kg of sodium 3-mercapto-1-propane sulfonate into a flask containing 100 kg of methanol and 10 kg of deionized water, stir evenly to obtain a mixed solution a, control the system to 70°C, and drop a mixed solution b consisting of 6.8 kg of allyltriethoxysilane, 68 kg of methanol and 0.64 kg of azobisisobutyronitrile into the flask. After the addition is completed, keep the temperature for reaction for 6 hours. After the reaction is completed, cool to room temperature, filter, wash the filter cake with cold methanol several times, and dry it in vacuum at 50°C for 48 hours.
[0045] The preparation steps of nitrogen-phosphorus-based siloxane are the same as those in Example 1.
[0046] Comparative Example 1
[0047] This embodiment provides a modified four-needle zinc oxide whisker, and the preparation steps are as follows:
[0048] 0.2 kg of tetrapod-shaped zinc oxide whiskers, 1 kg of acetic acid aqueous solution and 5 kg of anhydrous ethanol were added to a flask, and after ultrasonic dispersion for 1 hour, the temperature was controlled at 70° C., 2 kg of hyperbranched monomer was added, and the reaction was kept warm for 24 hours. The filter cake was washed with distilled water and then vacuum dried at 60° C. The mass fraction of the acetic acid aqueous solution was 66.7%, and the hyperbranched monomer was composed of γ-glycidyloxypropyltrimethoxysilane and nitrogen-phosphorus-based siloxane in a mass ratio of 1:1. The preparation steps of nitrogen-phosphorus-based siloxane were the same as those in Example 1.
[0049] Comparative Example 2
[0050] This embodiment provides a modified four-needle zinc oxide whisker, and the preparation steps are as follows:
[0051] 0.2 kg of tetrapod-shaped zinc oxide whiskers, 1 kg of acetic acid aqueous solution and 5 kg of anhydrous ethanol were added to a flask, and after ultrasonic dispersion for 1 hour, the temperature was controlled at 70° C., 2 kg of hyperbranched monomer was added, and the reaction was kept warm for 24 hours. The filter cake was washed with distilled water and then vacuum dried at 60° C. The mass fraction of the acetic acid aqueous solution was 66.7%, and the hyperbranched monomer was composed of γ-glycidyloxypropyltrimethoxysilane and sulfonate siloxane in a mass ratio of 1:1. The preparation steps of sulfonate siloxane were the same as those in Example 1.
[0052] Comparative Example 3
[0053] This embodiment provides a modified four-needle zinc oxide whisker, and the preparation steps are as follows:
[0054] 0.2 kg of tetrapod-shaped zinc oxide whiskers, 1 kg of acetic acid aqueous solution and 5 kg of anhydrous ethanol were added into a flask, and after ultrasonic dispersion for 1 hour, the temperature was controlled at 70° C., 2 kg of hyperbranched monomer was added, and the reaction was kept warm for 24 hours. The filter cake was washed with distilled water and then vacuum dried at 60° C. The mass fraction of the acetic acid aqueous solution was 66.7%, and the hyperbranched monomer was γ-glycidyloxypropyltrimethoxysilane.
[0055] Comparative Example 4
[0056] This embodiment provides a modified four-needle zinc oxide whisker, and the preparation steps are as follows:
[0057] 0.2 kg of tetrapod-shaped zinc oxide whiskers, 1 kg of acetic acid aqueous solution and 5 kg of anhydrous ethanol were added into a flask, and after ultrasonic dispersion for 1 hour, the temperature was controlled at 70°C, 0.02 kg of γ-glycidyloxypropyltrimethoxysilane was added, and the reaction was kept warm for 24 hours. The filter cake was washed with distilled water and then vacuum dried at 60°C. The mass fraction of the acetic acid aqueous solution was 66.7%.
[0058] Example 3
[0059] A method for preparing a toughening functional masterbatch comprises the following steps:
[0060] The polylactic acid and the modified four-needle zinc oxide whisker of Example 1 were placed in a vacuum oven at 80° C. and dried for 0.5 h, then placed in a high-speed mixer and stirred at 900 rpm for 8 min, then transferred to a twin-screw extruder and extruded into granules to obtain a toughening functional masterbatch.
[0061] Among them, the mass ratio of polylactic acid and modified four-needle zinc oxide whisker is 90:10, the temperature of each zone of the twin-screw extruder is: zone 100°C, zone 2 170°C, zone 3 185°C, zone 4 185°C, zone 5 195°C, zone 6 195°C, zone 7 195°C, zone 8 195°C, zone 9 195°C, die head 200°C, and the feeding speed is 25rpm.
[0062] Example 4
[0063] A method for preparing a toughening functional masterbatch comprises the following steps:
[0064] The polylactic acid and the modified four-needle zinc oxide whisker of Example 2 were placed in a vacuum oven at 80°C and dried for 0.8h, then placed in a high-speed mixer and stirred and mixed at a speed of 950rpm for 10min, then transferred to a twin-screw extruder, extruded and granulated to obtain a toughening functional masterbatch.
[0065] Among them, the mass ratio of polylactic acid and modified four-needle zinc oxide whisker is 88:12, the temperature of each zone of the twin-screw extruder is: 120°C in zone 1, 180°C in zone 2, 195°C in zone 3, 200°C in zone 4, 205°C in zone 5, 210°C in zone 6, 215°C in zone 7, 215°C in zone 8, 215°C in zone 9, 215°C in die head, and the feeding speed is 27rpm.
[0066] Example 5
[0067] A method for preparing a toughening functional masterbatch comprises the following steps:
[0068] The polylactic acid and the modified four-needle zinc oxide whisker of Example 2 were placed in a vacuum oven at 80° C. and dried for 1 hour, then placed in a high-speed mixer and stirred and mixed at a speed of 1000 rpm for 12 minutes, and then transferred to a twin-screw extruder for extrusion granulation to obtain a toughening functional masterbatch.
[0069] Among them, the mass ratio of polylactic acid and modified four-needle zinc oxide whisker is 85:15, the temperature of each zone of the twin-screw extruder is: 130°C in zone 1, 195°C in zone 2, 220°C in zone 3, 220°C in zone 4, 220°C in zone 5, 220°C in zone 6, 220°C in zone 7, 220°C in zone 8, 220°C in zone 9, 225°C in the die, and the feeding speed is 28rpm.
[0070] Comparative Example 5
[0071] A method for preparing a toughening functional masterbatch. Compared with Example 3, the modified four-needle zinc oxide whisker in Example 3 is replaced by the product prepared in Comparative Example 1, and the remaining raw materials and preparation process are the same as in Example 3.
[0072] Comparative Example 6
[0073] A method for preparing a toughening functional masterbatch. Compared with Example 3, the modified four-needle zinc oxide whisker in Example 3 is replaced by the product prepared in Comparative Example 2, and the remaining raw materials and preparation process are the same as in Example 3.
[0074] Comparative Example 7
[0075] A method for preparing a toughening functional masterbatch. Compared with Example 3, the modified four-needle zinc oxide whisker in Example 3 is replaced by the product prepared in Comparative Example 3, and the remaining raw materials and preparation process are the same as Example 3.
[0076] Comparative Example 8
[0077] A method for preparing a toughening functional masterbatch. Compared with Example 3, the modified four-needle zinc oxide whisker in Example 3 is replaced by the product prepared in Comparative Example 4, and the remaining raw materials and preparation process are the same as in Example 3.
[0078] The toughening functional masterbatch obtained in Example 3 to Example 5 and Comparative Example 5 to Comparative Example 8 was prepared according to the size of Type 1A in GB / T 1040.2-2006 and Type I in GB / T 1043.1-2008. Dumbbell-shaped and long strip specimens for tensile properties and impact toughness tests were prepared. The unidirectional tensile properties test was tested with a WDW universal testing machine according to GB / T1040.1-2006 (rate 2 mm / min), and the unnotched simply supported beam impact test was carried out on a TCJ-25J impact testing machine according to GB / T1043.1-2008 (span 60 mm). The results were taken as the average value of 5 groups of specimens, and the oxygen index was tested with reference to the standard GB / T 2406.1-2008. The results are shown in Table 1:
[0079] Table 1
[0080]
[0081] It can be seen from Table 1 that compared with the test results in Comparative Examples 5 to 8, the functional toughening masterbatch obtained in Example 3, Example 4, and Example 5 has higher comprehensive performance, indicating that the functional toughening masterbatch prepared by the present invention not only has good toughness, but also has good flame retardant properties.
[0082] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a toughening functional masterbatch, characterized in that: The following steps are involved: The polylactic acid and the modified four-needle zinc oxide whisker are placed in a vacuum oven at 80°C for drying for 0.5-1h, placed in a high-speed mixer, stirred and mixed for 8-12min, extruded and granulated to obtain a toughening functional masterbatch; The modified tetrapod-shaped zinc oxide whisker is a tetrapod-shaped zinc oxide whisker grafted with a hyperbranched polysilane, and the hyperbranched polysilane is obtained by hydrolyzing and condensing γ-glycidyloxypropyltrimethoxysilane, sulfonate-based siloxane and nitrogen-phosphorus-based siloxane; The preparation steps of sulfonate siloxane are as follows: Add sodium 3-mercapto-1-propane sulfonate to a flask filled with methanol and deionized water, stir evenly to obtain a mixed solution a, control the system to 70°C, and drop a mixed solution b consisting of allylsiloxane, methanol and azobisisobutyronitrile into the flask. After the addition is completed, keep the temperature for reaction for 4-6 hours. After the reaction is completed, cool to room temperature, filter, wash the filter cake with cold methanol several times, and dry it in a vacuum at 50°C for 48 hours.
2. The method for preparing a toughening functional masterbatch according to claim 1, characterized in that: The preparation steps of modified tetrapod-shaped zinc oxide whiskers are as follows: Add tetrapod-shaped zinc oxide whiskers, acetic acid aqueous solution and anhydrous ethanol into a flask, disperse by ultrasonic for 1 hour, control the temperature at 70-75°C, add hyperbranched monomer, keep the temperature for 24 hours, filter, wash the filter cake with distilled water and dry it under vacuum at 60°C.
3. The method for preparing a toughening functional masterbatch according to claim 2, characterized in that: The mass ratio of tetrapod-shaped zinc oxide whiskers, acetic acid aqueous solution, anhydrous ethanol and hyperbranched monomer is 0.2:1:5-10:2, the hyperbranched monomer is composed of γ-glycidyloxypropyltrimethoxysilane, sulfonate-based siloxane and nitrogen-phosphorus-based siloxane in a mass ratio of 1:0.2-0.4:0.6-0.8, and the mass fraction of acetic acid aqueous solution is 60-70%.
4. The method for preparing a toughening functional masterbatch according to claim 1, characterized in that: The molar ratio of sodium 3-mercapto-1-propane sulfonate to allylsiloxane is 1:1, and the amount of azobisisobutyronitrile is 5% of the total mass of sodium 3-mercapto-1-propane sulfonate and allylsiloxane.
5. The method for preparing a toughening functional masterbatch according to claim 1, characterized in that: The mass ratio of sodium 3-mercapto-1-propane sulfonate, methanol and deionized water in the mixed solution a is 5-6:100:
10.
6. The method for preparing a toughening functional masterbatch according to claim 1, characterized in that: The amount of methanol in the mixed solution a is 10 times the mass of allyl siloxane.
7. The method for preparing a toughening functional masterbatch according to claim 1, characterized in that: The allylsiloxane is allyltrimethoxysilane and / or allyltriethoxysilane.
8. The method for preparing a toughening functional masterbatch according to claim 1, characterized in that: The mass ratio of polylactic acid to modified tetrapod-shaped zinc oxide whisker is 85-90:10-15.
9. A toughening functional masterbatch, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation of epoxy-terminated hyperbranched polyester modified nano silica organic-inorganic hybrid material
CN106565963A
High-toughness polylactic acid composite material and preparation method thereof
CN113604019A